PENGARUH FAKTOR INDIVIDU, IBU DAN LINGKUNGAN TERHADAP PREVALENSI BALITA PENGIDAP INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2013 - Belawan, Arista Roza; Harsanti, Titik (E-Journal Widya Kesehatan dan Lingkungan, 2018)
Acute Respiratory Infection (ARI) is one of the major causes of under-five children’s morbidity and mortality in the world - both in developed countries and in developing countries - including Indonesia. Based on RISKESDAS 2013 data, the prevalence of ARI under five children aged is 25.8 percent in which NTT is a province with the highest prevalence of ARI in Indonesia. The purpose of this study was to determine the factors that influence the prevalence of children living with ARI in NTT. The methods used are descriptive and binary logistic regression using data Riskesdas 2013. The results showed that age, parental smoking status, type of household cooking fuel and area of residence classification affect the status of ARI in infants. More specifically, the tendency of children to suffer from ARI occurs in infants 1-4 years, have smoker parents, stay at home with less good cooking fuel (kerosene, charcoal and firewood) and live in rural areas.